Advances in ECM Protein-Based Materials - Ghorbani, Farnaz; Davari, Niyousha; Liu, Chaozong; Ghalandari, Behafarid (Springer International Publishing, 2024)
Proteins are the main building blocks of cell structure that play a vital role in the development of cell skeletons, cell differentiation, immunomodulation, and biomimetic features. The ability to modify the sequence of proteins to improve the macroscopic properties of final constructs has made them green materials for biomedical applications over the past decade. Within this context, extracellular matrix (ECM) proteins have received more attention due to their specific structural features and biological functions. This chapter provides an overview on the structure of the proteins found in the ECM within the human body. We will discuss protein self-assembly classifications in order to develop a comprehensive understanding of how protein-based materials can be employed in the near future. In the subsequent section, we examine the recent biomaterial developments involving ECM-derived protein-based materials. Moreover, to expand future research, we highlight the common aspects crucial for translational research relating to ECM-derived proteins.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Collagen; ECM; Elastin; Fibronectin; Laminin; Protein; Proteoglycan